Conceptual design of long‐cycle boron‐free small modular pressurized water reactor with control rod operation. (3rd April 2020) - Jang, Jaerim; Choe, Jiwon; Choi, Sooyoung; Lemaire, Matthieu; Lee, Deokjung; Shin, Ho Cheol
Summary: This paper presents a new conceptual design of soluble‐boron‐free small modular pressurized water reactor (SMPWR) core with the following singular features: long operation cycle, axially heterogeneous adjuster control rods, and ring‐type burnable absorbers (R‐BAs) coated on the outside of cladding materials. The core loads 37 Westinghouse‐type 17 × 17 fuel assemblies (FAs) of active fuel height 200 cm and produces 180 MW of nominal thermal power during a cycle length of 1555 effective full power days (EFPDs). Three types of burnable absorbers (BAs) are used to address the excess reactivity and obtain a long cycle: 2 w/o and 8 w/o enriched Gd2 O3 integral‐type BA (IBA), natural gadolinium R‐BA, and 80 w/o enriched 10 B Al2 O3 /B4 C wet annular burnable absorber (WABA). Two types of 200 cm long axially heterogeneous adjuster control rods are used to control the reactivity and the offset in axial power distribution. The first rod type adopts HfB2 with 80 w/o enriched 10 B for the bottom 140 cm and stainless steel for the top 60 cm. The second rod type uses HfB2 (natural boron) for the bottom 100 cm and HfB2 (80 w/o enriched 10 B) for the top 100 cm. A detailed safety parameter analysis is conducted to verify the imposed design limits, namely, axial shape index of less than ±0.4, 3D power peaking factor of smaller than 5.09, required shutdown margin of greater than 3000 pcm, and negative isothermal temperature coefficient during the entire reactor operation. It is successfully demonstrated that the proposed novel SMPWR design satisfies all the design limits and the target cycle length of 1500 EFPDs. Abstract : A small modular pressurized water reactor (SMPWR) core is designed with the following singular features: along operation cycle, ring‐type burnable absorber coated outside of cladding materials and axially‐heterogeneous adjuster control rods. The core loads 37 Westinghouse‐type 17×17 fuel assemblies of active fuel height 200 cm and produces 180 MW nominal thermal power. It is successfully demonstrated that the suggested novel SMPWR design meets all the design limits and the target cycle length of 1, 500 effective full power days.